Factors Associated with the Activeness of Posyandu Cadres in Providing Supplementary Food in Banyuasin District - Apriliani, Ferenadia; Fajar, Nur Alam; Rahmiwati, Anita; Flora, Rostika; Zulkarnain, Mohammad; Sunarsih, Elvi; Lubis, Adelina Irmayani (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2025)
Background: Stunting is a condition of failure to thrive in toddlers (babies under the age of five) due to chronic malnutrition, causing children to have a shorter height than they should for their age. Banyuasin Regency has the third highest prevalence of stunting in South Sumatra Province (13.3% in 2022). The Supplementary Feeding Program (PMT) is designed to improve the nutritional status of under-fives, and posyandu cadres play an important role in its successful implementation. This study aims to analyze the factors associated with the active role of posyandu cadres in providing supplementary food in Banyuasin Regency.Method: Quantitative research with a cross-sectional design using 100 samples with the Proportional random sampling method which was carried out in early October - early November 2024 in Banyuasin Regency.Result: The results of the chi square test showed that knowledge (p = 0.001), attitude (p = 0.025), age (p = 0.039), education (p = 0.524), incentives (p = 0.269), training (p = 0.019), length of time as a cadre (p = 0.045) facilities and infrastructure (p = 0.090) and active cadres as many as 59 posyandu cadres. This study indicates that the better the cadres’ knowledge, attitudes, and experience, and the more frequently they attend training, the more likely they are to play an active role in implementing the PMT program. In contrast, educational background, the provision of incentives, and the availability of facilities do not necessarily influence the cadres’ active involvement in the delivery of the PMT program. Efforts to increase the training of posyandu cadres are the main recommendations to support the success of the PMT program in stunting prevention in Banyuasin district.